A new species of the genus Boulenophrys from South China (Anura, Megophryidae) - Wang, Jian; Lin, Shi-Shi; Gan, Jun-Shen; Chen, Hong-Hui; Yu, Ling-Min; Pan, Zhong; Xiao, Jia-Jie; Zeng, Zhao-Chi (Zootaxa, 2024)
In this study, a new species of the genus Boulenophrys is described from northwestern Guangdong, within the Nanling Moutains. The new species can be distinguished from all known congeners by a combination of morphological characteristics and the mitochondrial genetic divergence. The new species is found to breed in winter season which was not common in most amphibian groups but also present in some Boulenophrys congeners. We further discuss the inadequate surveys for these species due to the oversight of such multi-seasonal breeding pattern.